Carrion Salazar, B (2022)Optimización del sistema de gestión en seguridad y salud ocupacional Gestión administrativa y gestión del talento humano de las clínicas odontológicas institucionales. Tesis de Pregrado) Universidad Nacional d Chimborazo, Riobamba, Ecuador - Carrion Salazar, Blanca Elizabeth (2022)
ABSTRACT In recent years, safety and health at work has become the main basis for compliance with Ecuadorian national regulations, from the Magna Carta to the internal regulations of each company or institution. The Labor Ministry, the Social Security Ecuadorian Institute, are the governing bodies for promoting and supervising development of the Occupational Health and Safety Management System at national level. For this reason, the National University of Chimborazo, safeguarding compliance with the law in the area of institutional dental clinics, looks for the feasibility of optimizing the occupational health and safety management system in its four pillars based on the Andean Instrument of Safety and Occupational Health (Resolution 957). In the proposal presented in this research, with development components, it is suggested to elaborate the pillars of Administrative Management and Human Talent Management, through the correlational and non-experimental methodology, seeking to determine if the optimization of the Occupational Health and Safety System, both in administrative management and human talent management of the Institutional Dental Clinics, will solve the problems that are present in the study area. Obtaining as a final result, the required documents to provide an efficient and suitable system that allows to guarantee safe work environments. Keywords: Administrative Management, Human Resources Management, Occupational Health and Safety, Safety Management, Work Environment..